Characterization of a New Immunosuppressive and Antimicrobial Peptide, DRS-DA2, Isolated from the Mexican Frog, Pachymedusa dacnicolor - Claire Lacombe; Estefania Aleman-Navaro; Thierry Drujon; Veronica Martinez-Osorio; Emmanuelle Sachon; Erika Melchy-Pérez; Ludovic Carlier; Lorena Elizabeth Fajardo Brigido; Yannick Fleury; Christophe Piesse; Guadalupe Gutiérrez-Escobedo; Alejandro De las Peñas; et al. (International Journal of Inflammation, 2024)
Inflammatory and antimicrobial diseases constitute a major burden for society, and fighting them is a WHO strategic priority. Most of the treatments available to fight inflammatory diseases are anti-inflammatory drugs, such as corticosteroids or immunomodulators that lack cellular specificity and lead to numerous side effects. In addition to suppressing undesired inflammation and reducing disease progression, these drugs lessen the immune system protective functions. Furthermore, treating infectious diseases is more and more challenging due to the rise of microbial resistance to antimicrobial drugs. Thus, controlling the inflammatory process locally without compromising the ability to combat infections is an essential feature in the treatment of inflammatory diseases. We isolated three forms (DRS-DA2N, DRS-DA2NE, and DRS-DA2NEQ) of the same peptide, DRS-DA2, which belongs to the dermaseptin family, from the Mexican tree frog Pachymedusa dacnicolor. Interestingly, DRS-DA2N and DRS-DA2NEQ exhibit a dual activity by inducing the death of leukocytes as well as that of Gram-negative and Gram-positive bacteria, including multiresistant strains, without affecting other cells such as epithelial cells or erythrocytes. We showed that the death of both immune cells and bacteria is induced rapidly by DRS-DA2 and that the membrane is permeabilized, leading to the loss of membrane integrity. We also validated the capacity of DRS-DA2 to regulate the pool of inflammatory cells in vivo in a mouse model of noninfectious peritonitis. After the induction of peritonitis, a local injection of DRS-DA2N could decrease the number of inflammatory cells locally in the peritoneal cavity without inducing a systemic effect, as no changes in the number of inflammatory cells could be detected in blood or in the bone marrow. Collectively, these data suggest that this peptide could be a promising tool in the treatment of inflammatory diseases, such as inflammatory skin diseases, as it could reduce the number of inflammatory cells locally without suppressing the ability to combat infections.